NH4 : NO3 nutrition influence on biomass productivity and root respiration of poplar and willow clones. Issue 1 (31st October 2014) - Rewald, Boris; Kunze, Martin E.; Godbold, Douglas L.
Abstract: Nitrogen fertilization often improves the yield of intensively managed, short‐rotation coppices. However, information of N nutrition form on the growth of common species and clones used for biomass production is limited. Thus, this study aims at evaluating N form effects on the growth of two Salicaceae clones. Cuttings of the poplar clone Max 4 ( Populus maximovizcii × P. nigra ) and the willow clone Inger ( Salix triandra × S. viminialis ) were fertilized in a pot experiment with four ratios of nitrate (NO3 − ) to ammonium (50%, 62.5%, 75% and 87.5% NO3 − balanced with ammonium (NH4 + ) to constant total N) for one growing season and under stable soil pH. Plants were harvested for analysis of biomass and morphology of leaves, stem and roots. Respiration of fine and coarse roots (RR) was determined and related to biomass growth. Salix cv. Inger accumulated more total dry matter than Populus cv. Max 4. In both Salicaceae clones, the total biomass was significantly influenced by the nitrate ratio and greatest in plants fertilized with 50% NO3 − of the total N supply. Both clones possess a different leaf and root morphology, but no significant influence of the NO3 − ratio on the morphology was found. Fine RR rates differed significantly between clones, with significantly greater fine RR in Max 4; 87.5% NO3 − fertilization increased the fine RR. Fine RR and total accumulated plant biomass were closely related. Our study is the first to show the tremendous influence of fine root respiration, especially including the carbon‐intensive reduction of NO3 − to NH4 +, on the aboveground growth of Salicaceae clones. Ways to improve yield in SRC are thus to lower the assimilate consumption by fine roots and to match fertilization regimes to the used clones or vice versa.